Role of Secondary Prophylaxis With Valganciclovir in the Prevention of Recurrent CMV Disease in Solid Organ Transplant Recipients - Gardiner, Bradley. (2017)
Abstract: Reactivation of latent cytomegalovirus (CMV) infection is a major cause of morbidity and mortality in solid organ transplant recipients (SOTR). Ganciclovir and valganciclovir are highly effective antiviral drugs whose role in the treatment of CMV disease and primary prophylaxis is well established. The efficacy of secondary prophylaxis following the successful completion of CMV treatment is, however, not clear. The objectives of this study were to examine the effect of secondary prophylaxis with valganciclovir on the likelihood of relapse in SOTR who had completed treatment for an episode of CMV disease. We performed a single-center retrospective cohort study of SOTR from 1995-2015 and used propensity score based inverse probability of treatment weighting methodology to control for confounding by indication. A weighted Cox proportional hazards model was created to determine the effect of SP on time to relapse within 1 year of treatment completion. A total of 170 heart, liver and kidney transplant recipients who were treated for an episode of CMV disease were included. One hundred and twenty (70.6%) received SP for a median duration of 61 days, with a range of 5 to 365 days. Thirty-nine patients (23%) relapsed. Use of SP was protective against relapse from 0 to 6 weeks following treatment completion (hazard ratio, HR 0.19, 95% CI 0.05-0.69) but after this period of time, risk of relapse did not significantly differ between the two groups (HR 1.18, 95% CI 0.46-2.99). Our findings demonstrate that patients who received SP with valganciclovir were significantly less likely to relapse during the initial 6 week period following completion of treatment for CMV infection, but after this their risk of relapse was the same as those who did not receive SP. SP should be considered a potentially effective strategy in reducing ongoing morbidity and potentially mortality following CMV disease in SOTR.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Snydman.; Committee: Jennifer Chow, Lori-Lyn Price, Natalie Nierenberg, and David Kent.; Keywords: Medicine, and Virology.